Integrated Care and the Behavioral Health Home: A New Program to Help Improve Somatic Health Outcomes for Those With Serious Mental Illness. Issue 12 (December 2015) - Maragakis, Alexandros; RachBeisel, Jill
Abstract : Abstract: Research indicates that individuals with serious mental illness (SMI) consistently have lower access to primary care and much higher rates of preventable somatic health problems, like diabetes, hypertension, and hyperlipidemia. These higher rates of preventable somatic health problems result in poorer quality of life, lower life expectancy, and higher use of expensive emergency care. With this growing awareness and the recent health care reform, a new program, called the Behavioral Health Home (BHH), has been created to reduce barriers that individuals with SMI face when trying to access primary care. This report provides information on the how these health disparities were well documented at a university-based psychiatric clinical program and the creation of a BHH to help address these health needs. Lessons learned from initial implementation and future directions of the BHH are discussed.